(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. This article examines the theoretical and practical principles of institutional and institutional prerequisites for ensuring the development of regional natural gas distribution operators in modern economic conditions. The author’s position on the substantiation of the high level of importance and relevance of the role of the institutional environment in the structure of ensuring the maximum level of efficiency of the process of development of regional gas distribution networks was also reflected. All possible manifestations of maximum efficiency in the main and additional activities of gas distribution network operators in the Western region of Ukraine are outlined. It was proved that it is the developed form of institutional support and the environment that covers the presence of the required institutions, as well as mutually harmonizes them. This aspect affects the internal business processes that take place in the activities of regional gas distribution companies, their organizational and technical development, as the formation of the image at the interregional and international levels, as well as increasing the quality and reliability of distribution services among natural gas consumers. As a result of the study of the institutional basis, as well as the nature of institutions and their possible impact on the efficiency of gas distribution organizations in the western region, the latter was conditionally divided into basic and related activities. The purpose of the article. Research of institutional preconditions for ensuring the development of regional gas distribution network operators. Results. It is known that today the level of stability of the environment of gas distribution companies in Ukraine is insufficient, at the same time their regional position is unbalanced, which in turn implies the need to find new directions and mechanisms to help overcome various crises and trends on the way to highly efficient and unhindered their development. It is the aspect that Ukrainian regional gas distribution companies are an important component of national energy security and independence, including the stable and continuous supply of consumer demand in the natural gas distribution market, at the same time have almost always a monopoly position and is the center for the implementation of speculative decisions at the highest state level, necessitates large-scale development of institutional support to regulate their activities with the obligation to the delineation of the boundaries of potential development. An important aspect of the future development of regional gas distribution companies in a rather unstable operating environment is the creation of a broad-based institutional environment that will ensure balance and regulate relations between the consumer sector, government institutions, and the gas distribution companies themselves. At the same time, it will create appropriate conditions for the constant increase in the level of competitiveness of the latter. From this, we can conclude that institutional efficiency is directly dependent on the aspect - who exactly ensures their creation and further control of their functioning. After all, the degree of functional efficiency and further successful development of regional gas distribution network operators in Ukraine will depend on how skillfully the country will create equal conditions for absolutely all participants of the natural gas distribution market by implementing institutional incentives and restrictions. Thus, it is the institutional form of the approach to ensuring the further development of regional gas distribution organizations that is focused on the study of institutions and institutions that contribute to the regulation of their activities. In other words, the institutional form of regulating the activities of regional gas distribution network operators is a directed activity of natural gas distribution market participants, which to some extent affects the functioning and further development of gas distribution companies in the region towards continuous improvement of their structure, overall strategy, and management system. , common values, etc .; including taking into account the impact of social, economic, legal, and political institutions in the face of various kinds of instability. Quite important in the process of institutionalization of the process of functioning of gas distribution companies are market institutions and institutes, including: financial, infrastructural, legal and functional; private property; competition. We offer a study of the prospects for the introduction of possible changes in the activities of regional gas distribution companies because of established institutional dogmas. Today, it is not effective enough, and in some regions of Ukraine there is no form of state support for the implementation of relevant programs of innovation and scientific and technological progress has led to a significant deterioration in the distribution of natural gas consumers. After all, there is still a high level of wear of gas distribution networks and their significant resource and energy consumption, there are no innovative solutions. Among the reasons that led to such a market position of regional gas distribution companies is the lack of institutional support, which is the lack of proper foundations for the implementation of innovative solutions, lack of necessary material and financial support to update technological solutions in production, corruption, etc. Today, due to the lack of normal and functional institutional support, there are no proper contractual processes that would be established between suppliers and consumers of natural gas in the regions based on transparency. In our opinion, the formation of institutional approaches and tools for their implementation will increase the efficiency of gas distribution companies in the region, improve the quality of services provided, and will stimulate all participants in the distribution market among natural gas consumers in the region. It is also worth noting that the vast majority of regional gas distribution companies are part of a rather complex "vertical" structure. In turn, as is known from the course of institutional theory, under the conditions of the vertical form of structural construction of the enterprise, there is also a fairly high level of possible costs for its management. Conclusions. It is important to note that the institutional environment, which will be expressed in the presence of all necessary institutions, as well as their coherence with each other today, is a significant and dominant entity in terms of ensuring maximum efficiency and further development of gas distribution companies in the western region of Ukraine. We believe that the most effective and functioning institutional environment will create conditions for maximizing the level of internal processes at gas distribution companies; the most effective organizational and technological development; harmonizes mutual relations between all market participants.